ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH CABANG KOTA LHOKSEUMAWE (Studi Kasus Bank BRI Dan Bank BRI Syariah) - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2019)
The problem discussed in this study is the comparison of the financial performance of Bank Mandiri (Persero) Tbk, with Bank Syariah Mandiri, for the period 2008-2012. The purpose of this study is to compare the financial performance of Bank Mandiri (Persero) Tbk, with Bank Syariah Mandiri, for the period 2008-2012. In this study, the method used is descriptive data analysis. Based on the results of the study obtained the following results. Descriptive analysis shows that the Capital Adequacy Ratio (CAR) of the two banks meets the standard, which is above 8%. Both banks' Non Performing Loans (NPL) ≤ 5% so that they enter good standards according to Bank Indonesia. Both banks' return on Assets (ROA) ≥ 1.5% so that they meet Bank Indonesia standards. The two banks' loan to deposit ratio (LDR) is between 85% -110% and thus meets Bank Indonesia standards. The two banks' Operational Expenses to Operating Income (BOPO) ratio <92%, thus meeting Bank Indonesia standards.